BIOLOGICAL CONTROL OF THE TOMATO LEAFMINER IN ALGERIA: EFFICACY OF TWO NATIVE PARASITOIDS IN OPEN-FIELD TRIALS - N. Laadel; S. Guettaf; A. Benmerzoug; N. Benzidane; Z. Boulgueraguer; F. Bensebaa; A. Harrar; K. Ghit; A. M. Abu-Elsaoud; W. Elfalleh6and H. Bendif (Journal of Animal and Plant Sciences, 2026)
The tomato leafminer, Tuta absoluta has emerged as a major pest threatening tomato production in Algeria, with intensive pesticide use resulting in resistance development and environmental concerns. This study assessed the efficacy of two native parasitoid species Trichogramma bourarachae (egg parasitoid) and Bracon nigricans (larval parasitoid) for the biological control of T. absoluta under open-field conditions in Sétif, Algeria. Over two growing seasons (2022–2023), parasitoids were released in ten tomato fields (1 ha each) at a rate of 50,000 wasps per ha, while five control fields were managed using conventional pesticide applications. T. bourarachae achieved up to 70% egg parasitism, and B. nigricans parasitized approximately 65% of larvae, resulting in a 60–70% reduction in T. absoluta populations compared to controls (p < 0.001). Peak efficacy was observed mid-season (weeks 6–10), coinciding with the highest pest pressure. Tomato yields in parasitoid-treated plots increased by 30–40% (45,000 vs. 32,000 kg/ha; p < 0.001), with a 20% improvement in marketable fruit quality. Pesticide use was reduced by half (three vs. six applications per season), lowering pest management costs by 50% (75 vs. 150 USD/ha). Economic analysis indicated a 25% increase in net profits in treated plots (1,500 vs. 1,200 USD/ha), attributable to higher yields and reduced pesticide inputs. The results demonstrate the effectiveness of native parasitoids in controlling T. absoluta and highlight their potential integration into sustainable IPM programs in Mediterranean tomato production systems. Further research should focus on optimizing mass-rearing techniques and expanding field trials to other regions.
Keywords: Agroecosystem management; Augmentative releases; Economic feasibility; Indigenous natural enemies; Integrated pest management; Parasitoid efficacy; Pesticide reduction; Solanaceous crops; Sustainable agriculture; Yield enhancement.